2022
DOI: 10.1186/s13195-022-01116-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a fully-automated Lumipulse plasma phospho-tau181 assay for Alzheimer’s disease

Abstract: Background The recent promise of disease-modifying therapies for Alzheimer’s disease (AD) has reinforced the need for accurate biomarkers for early disease detection, diagnosis and treatment monitoring. Advances in the development of novel blood-based biomarkers for AD have revealed that plasma levels of tau phosphorylated at various residues are specific and sensitive to AD dementia. However, the currently available tests have shortcomings in access, throughput, and scalability that limit wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
(44 reference statements)
2
20
0
Order By: Relevance
“…The accuracy of pTau 181 in plasma has been previously studied in the Lumipulse and different accuracies have been reported to differentiate CU from AD. While Janelidze et al reported an AUC of 0.7 [17] Wilson et al found an accuracy of 0.96 [24]. In our study, we found a global accuracy of 0.91 for pTau 181 .…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The accuracy of pTau 181 in plasma has been previously studied in the Lumipulse and different accuracies have been reported to differentiate CU from AD. While Janelidze et al reported an AUC of 0.7 [17] Wilson et al found an accuracy of 0.96 [24]. In our study, we found a global accuracy of 0.91 for pTau 181 .…”
Section: Discussionsupporting
confidence: 40%
“…The performance of plasma markers to discriminate patients with AD from cognitively unimpaired participants, patients with other dementias and with not degenerative dementias has been assessed in previous studies using other analytical platforms, with AUCs ranging from 0.70 to 0.96 for pTau 181 [7,17,[23][24][25][26][27], and from 0.64 to 0.86 for Aβ 1-/Aβ 1-40 [5,8,10]. Most of the studies reported better accuracies with the use of composite measures that combined two or more markers and/or clinical or genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that plasma p‐tau181 levels might indicate AD pathology even before Aβ biomarkers reach the positivity threshold 34,35 . However, most studies have relied on longer follow‐up periods (over 2 years) when evaluating the relationship between plasma p‐tau181 and cognitive or structural brain outcomes 6,24,36 . Our null findings suggest that plasma p‐tau181 might correlate with these measures later in the disease process.…”
Section: Discussionmentioning
confidence: 68%
“…34,35 However, most studies have relied on longer followup periods (over 2 years) when evaluating the relationship between plasma p-tau181 and cognitive or structural brain outcomes. 6,24,36 Our null findings suggest that plasma p-tau181 might correlate with these measures later in the disease process. In addition, sample Some of the previous studies have investigated the relationship between plasma p-tau181 and cognitive performance in cohorts of CU older adults with a higher risk of developing AD, for example, cohorts originating from memory clinics and enriched with APOE ε4 carriers or with evidence of subjective cognitive decline (SCD) at baseline.…”
Section: Discussionmentioning
confidence: 68%
“…Separate aliquots processed by the Lumipulse G system (Fujirebio US, Inc., Malvern, PA) were used to measure CSF levels of AD biomarkers (phosphorylated tau 181 [p-tau 181 ], Aβ 42 , and Aβ 40 ) for all 147 SAMS CU and 89 of the 111 ADRC+ participants. 29 The remaining…”
Section: Ad Biomarker Quantification and Amyloid Status Determinationmentioning
confidence: 99%